Screening of immuno-modulatory potential of different herbal plant extracts using striped catfish (Pangasianodon hypophthalmus) leukocyte-based in vitro tests. Issue 93 (October 2019) - Nhu, Truong Quynh; Bich Hang, Bui Thi; Vinikas, Anais; Bach, Le Thi; Buu Hue, Bui Thi; Thanh Huong, Do Thi; Quetin-Leclercq, Joëlle; Scippo, Marie-Louise; Phuong, Nguyen Thanh; Kestemont, Patrick
Abstract: Many medicinal plants have been shown to possess biological effects, including immuno-modulatory activities on human and other mammals. However, studies about the potential mechanisms of plant extracts on the humoral and tissular immunities in fish have received less attention. This study aimed to screen the immunestimulating properties of 20 ethanol plant extracts on striped catfish Pangasianodon hypophthalmus leukocytes. The peripheral blood mononuclear cells (PBMCs) and head kidney leukocytes (HKLs) of striped catfish (50 ± 5 g per fish) were stimulated at 10 and 100 μg of each plant extract per mL of cell culture medium. Several humoral immune parameters (lysozyme, complement and total immunoglobulin) were examined at 24-h post stimulation (hps). Furthermore, the responses of four cytokine genes, namely il1β, ifrγ 2a and b, and mhc class II were assessed by quantitative real-time PCR at 6, 12, 24, and 48 hps. The results showed that lysozyme, complement as well as total immunoglobulin levels in both PBMCs and HKLs were regulated by some of the plant extracts tested in a concentration-dependent manner; some plant extracts induced the highest immune responses at the low dose (10 μg mL −1 ) while others were more efficient at high dose (100 μg mL −1 ). Among the extracts, five extracts including garlic Allium sativum L. (As), neem Azadirachta indica A. Juss (Ai), asthma-plant Euphorbia hirta L. (Eh), bhumi amla Phyllanthus amarus Schum. et Thonn (Pa), and ginger Zingiber officinale Rosc (Zo) induced significant changes in the expression of pro-inflammatory cytokine ( il1β ), antiviral cytokines ( ifrγ 2a and b) and adaptive immune cytokine ( mhc class II) in striped catfish cells. Pa always modulated the strongest expression of the four cytokines in PBMCs and HKLs over the whole experimental period ( p < 0.05), whereas Zo did not stimulate the mhc class II expression in striped catfish leukocytes throughout experimental periods. These in vitro results demonstrated that some plant extracts could differently modulate great potential immune response in fish, supporting their applications in further in vivo experiments. Highlights: Plant extracts modulated humoral immune parameters in striped catfish leukocytes by in vitro test. Different plant extracts regulated differently potential immune response in striped catfish. Ethanol plant extracts stimulated striped catfish immune system by affecting PBMCs and HKLs. il1β, ifrγ 2a and b, and mhc class II genes were regulated in leukocytes during in vitro extract-stimulation.